Effect of footstrike pattern on running economy at a fast speed - Terasaki, N.; Suzuki, T.; Ogane, R.; Shioda, K.; Kinugasa, R. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: No difference in running economy between rearfoot and forefoot strike patterns has been observed in four previous studies (Ardigò et al. 1995; Cunningham et al. 2010; Gruber et al. 2013; Perl et al. 2012). However, these previous studies comparing running economy between footstrike patterns were limited by over a range of a slow to medium (~ 15 km/h) speeds. The present study was therefore to determine whether there were differences in running economy between footstrike patterns at a fast speed. Methods: Six male habitual forefoot runners performed the rearfoot and forefoot patterns on a treadmill at 10 and 18 km/h while wearing standard running shoes. Steady-state rate of oxygen consumption was determined for each footstrike and speed conditions. After 2 min of habituation, subjects performed four trials in a random order. Each trial lasted a minimum of 3 min, with at least 1 min of running after VO2 levels reached a steady-state. Running economy was expressed as the rate of VO2 (ml/kg/min). Results: No significant difference in VO2 was observed between footstrike patterns at a slow and fast speeds. VO2 was 33.7 ± 1.3 ml/kg/min for the forefoot strike and 34.3 ± 2.2 ml/kg/min for the rearfoot strike at the slow speed while VO2 was 56.9 ± 4.4 ml/kg/min for the forefoot strike and 57.1 ± 3.4 ml/kg/min for the rearfoot strike at the fast speed. Discussion: We predicted that foot strike types affect running economy at a fast speed. This hypothesis is based on idea that performing the nonhabitual pattern resulted in artificially high rates of VO2 given that performing a novel task typically causes an increase in the rate of VO2 and requires habituation to observe any improvement in economy (Cavanagh & Williams 1982). Differences in running economy may be results of the different muscle activation patterns, elastic energy utilization in the Achilles tendon (Lieberman 2010), and force exerted by a muscle fibers that probably take longer to adapt to a new gait pattern than kinematic adjustments (Duchateau et al. 2006). However, the potential for predicted high VO2 as a result of performing a nonhabitual footstrike pattern was eliminated in our investigation, indicating the acute response to switching footstrike patterns in habitual forefoot runners may not appear to be any impact on running economy regardless of running speed. A long accommodation period may thus be required when examining metabolic differences between footstrike types.